(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Community library is a type of public library which serves as community builder, manager of diversity, centre for arts, culture and preservation of heritage, promotion of learning and socialization, promotion of democratic values and catalyst for addressing social problems. The effective performance of these functions through library holding, materials, resources and services is expected to yield social development in terms of: association engagement, intergroup cohesion, gender equality, cultural advancement and preservation, interpersonal safety and trust, building of democratic values, spread of education, increase awareness and socialization. Qualitative design was adopted in which three Focus Group Discussions were conducted consisting of ten participants each, with a total of thirty in urban and rural areas of Cross River State. Anchoring on Robert Merton Functional Theory, the study shows that influence of library functions was not widespread on indicators of social development, in order to invoke widespread social development of Cross River State and her people. It was recommended that more libraries be established, especially community libraries in rural areas, training of library personnel, renovation of existing libraries and updating library materials in order to bring about the desired social development.